2020
DOI: 10.3390/ijerph17093148
|View full text |Cite
|
Sign up to set email alerts
|

Generational Differences in Perceptions of Food Health/Risk and Attitudes toward Organic Food and Game Meat: The Case of the COVID-19 Crisis in China

Abstract: In December 2019, a novel laboratory-confirmed coronavirus (2019-nCoV) infection, which has caused clusters of severe illnesses, was first reported in Wuhan, the capital of Hubei province, China. This foodborne illness, which reportedly most likely originated in a seafood market where wild animals are sold illegally, has transmitted among humans through close contact, across the world. The aim of this study is to explore health/risk perceptions of and attitudes toward healthy/risky food in the immediate contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 67 publications
8
88
1
Order By: Relevance
“…Regarding the impact of COVID-19, approximately two-thirds of consumers reported that the pandemic has increased their green food purchase intentions because of their growing health concerns. This is in agreement with results from Ben Hassen et al [ 33 ] and Xie et al [ 28 ], in that the COVID-19 crisis influenced respondents’ perceptions of health and risk, which in turn changed consumers’ sensitivity and beliefs and resulted in a further increase in organic food consumption. However, these increasing intentions did not increase the final amount of green food purchases.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the impact of COVID-19, approximately two-thirds of consumers reported that the pandemic has increased their green food purchase intentions because of their growing health concerns. This is in agreement with results from Ben Hassen et al [ 33 ] and Xie et al [ 28 ], in that the COVID-19 crisis influenced respondents’ perceptions of health and risk, which in turn changed consumers’ sensitivity and beliefs and resulted in a further increase in organic food consumption. However, these increasing intentions did not increase the final amount of green food purchases.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the level of concern for Covid, a study [112] believes that those consumers who perceive greater risks change their buying behaviours more, which has also been observed in our results (Table 7). However, the fact that consumers in segment 3, who perceived a greater risk, still consider the price important, can be in line with the consideration that price restrictions are a consequence of the foreseeable economic crisis [29].…”
Section: Discussionsupporting
confidence: 86%
“…It could be that established brands, which are well positioned regarding the perception of quality of their products, work better than private brands, and that the result is in line with some authors [29], which says that well-positioned brands will have an advantage during pandemics. Furthermore, authors [112] says that in situations of risk, consumers prefer to buy organic products. The price, which decreased in importance for segment 2 and remained stable for segment 3, in other studies [42] was seen as an indicator of the quality of the product, meaning it is a significant attribute, while revealing that a high price increases consumer confidence.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, the transportation of animal feeds and food, including animal production products, encountered many obstacles. For instance, in China, milk transport was disrupted by tight road traffic controls, leading to milk dumping (85). Moreover, import and export difficulties by maritime transport, linked to several factors such as lack of manpower in Chinese ports, minimum time at sea imposed by certain ports on ships from China seriously disturbed the transport of animal products between China and neighboring countries.…”
Section: Effects On the Transport Of Animal Feeds And Animal Productimentioning
confidence: 99%